A proposal for the study of Physicochemical in Higher Education from a teaching resource (Research, Society and Development, 2020)
The present work aims to present the results of the application of a teaching strategy used to develop the formal contents provided for in the PhysicoChemical course. The activity was carried out with twelve students from a second semester class of the Pharmacy course at a Higher Education Institution in the Central Region of the state of Rio Grande do Sul. Through a didactic sequence, it was possible to explore some basic concepts of PhysicoChemical. A didactic sequence was developed with four stages developed over a semester, which sought to reflect and study in a dynamic and alternative way formal contents such as measurement units; physical and chemical phenomena; study of gases; chemical balance and factors that influence it; chemical kinetics and dispersed systems. For this purpose, a didactic resource was elaborated that enabled the interaction of students with the object of study and the development of skills and competences. It was found that in addition to providing teamwork and the sharing of different knowledge, the possibility of interaction with the object of study provides students with the ability to build knowledge from previous ideas, complexify them and apply them in different contexts. The educator enables the development of activities that privilege a learning process that increasingly requires the condition of a participatory subject, involved, motivated and active in the deconstruction and reconstruction of knowledge.